Changes in colonic contractility in response to inflammatory bowel disease: Long-term assessment in a model of TNBS-induced inflammation in rats - Calabresi, Marcos F. F. [UNESP]; Tanimoto, Alexandre [UNESP]; Prospero, Andre G. [UNESP]; Mello, Fabio P. F. [UNESP]; Soares, Guilherme [UNESP]; Di Stasi, Luiz C. [UNESP]; Miranda, Jose R. A. [UNESP] (Elsevier B.V., 2019)
Aims: Inflammatory bowel disease is a chronic relapsing inflammation that affects the gastrointestinal tract, causing changes in colonic motility. The evolution of these changes is not completely understood and possibly related to symptoms that appear in different degrees of the intestinal inflammation. Therefore, our aim is evaluate during 14 days of assessment aspects of colonic contractility using 2,4,6-trinitrobenzenesulfonic acid (TNBS) model of inflammation in rats and associate the inflammatory process with colonic motility. Methods: Contractility and inflammatory parameters were assessed in the same animal in six different moments: before intestinal inflammation induction, 2, 5, 8, 11, and 14 days after induction. The mechanical activity was determined by alternating current biosusceptometry (ACB) and subdivided into rhythmic propagating ripples (RPR) and rhythmic propulsive motor complexes (RPMC). We assessed inflammation by determining myeloperoxidase activity in feces. Results: Transient and permanent changes were observed in colonic motility as a function of the inflammatory process evaluated through myeloperoxidase activity. We identified two contraction profiles: RPR and RPMC. The microscopic analysis demonstrated a depth of damage caused by an injury that was associated with changes in motility. Conclusions: We implemented a robust and adequate (specific) signal processing to quantify two measured colonic frequency patterns. Thus, we performed a detailed temporal analysis of the consequences of TNBS-induced inflammation on colonic motility in rats. Our approach enables further long-term assessments in the same animal with different mechanisms and duration of injury, remission, treatments and their motor consequences.
Keywords: Inflammatory bowel disease; Colonic contractility; Alternating current biosusceptometry